Ensino religioso e cultura afro-brasileira : estudo de caso na comunidade Quilombola Mussuca/Laranjeiras-Sergipe - Costa, Ramon Diego Fonseca (2020)
The present study proposes to discuss Religious Education as an element related to the process of identity construction in a quilombola community, taking as a reference Law nº 10.639 / 03, which makes the teaching of Afro-Brazilian and African History and Culture mandatory. In this sense, it aims to analyze Religious Education - ER as a school subject, as well as the tensions between religion and affirmation of identity at the Municipal School Mayor José Monteiro Sobral, in the quilombola community Mussuca, Laranjeiras / SE. For this study, in the school environment, the emergence of a multicultural reality is perceived, implying tensions and conflicts denounced by the school community. Although religious pluralism is not a novelty, Christian religious institutions have always enjoyed hegemony, arising from their political relationship in the history of teaching in Brazil, such issues are still not overcome, but there is a glimpse of progress from a formal point of view with the Law of Directives and Bases of Education (Law nº 9.394 / 1996), specifically in the reformulation of article 33 (Law nº 9.475 / 1997) that implemented the RE in public schools. Thus, it is concluded that in relation to the religious field and the educational field, it is noticeable that Mussuca is currently a quilombola community that is culturally / religiously in conflict, as there has been a vertiginous growth of the different evangelical denominations and a decline of religions of African origin. The school curriculum is also marked by social / local expectations about it. If the community expects schools not to have such a debate, schools exempt themselves from doing so in order not to scratch the relations between school and the Community.